Study of some alcohol amounts in commercial alcoholic disinfectant solutions using gas chromatography with flame ionization detection - Darbanian, Masoumeh; Nezhadali, Azizollah; Rahimi, Vafa Baradaran (European Journal of Chemistry, 2022)
A simple solvent extraction method was used to analyze alcohol-based hand rubs (ABHRs) using gas chromatography with a flame ionization detector. 79 samples including 68 liquid and 11-gelled ABHRs were analyzed in the Food and Drug Laboratories Research Center of Mashhad, Iran. 17 samples had methanol, 50 samples had the correct percentage of alcohol (60-80%), and 12 samples had the incorrect percentage of alcohol (<60%). The RSD% of methanol, ethanol, and isopropanol were as 2.28, 2.18, and 1.52, respectively. The relative recoveries for methanol, ethanol, and isopropanol were 102.5, 97.8, and 114, respectively. All experiments were repeated three times. The limit of detection and the limit of quantification for methanol, ethanol, and isopropanol were obtained as 0.22, 0.24, 0.10 (%) and 0.71, 0.82, 0.68 (%), respectively.